Dynamics of Two Delays Differential Equations Model of HIV Pathogenesis with Absorption and Saturation Incidence - Sivakumar, Vinoth; Thippan, Jayakumar; Dhandapani, Prasantha Bharathi (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we proposed and analyzed time delays HIV pathogenesis model with absorption and saturation incidence. We derived the basic reproductive number R_0 which is used to show the stability of the disease-free and infected steady states. Further, we studied the effect of the time delay of the infected steady state. In addition, we examined the existence of Hopf bifurcation on infected steady-state and the model exhibits Hopf bifurcation by using delay as a bifurcation parameter. Numerical simulations are provided to illustrate the corresponding theoretical results.